Seed Viability, Imbibition Dynamics and Storability of Aegle marmelos (L.) Corrêa: Implications for Propagation and Conservation - MANISH KUMAR VIJAY (Seed Research, 2025)
The present investigation assessed seed viability, water imbibition behavior, pre-treatment requirements, and storability of Aegle marmelos (L.) Corrêa. Seed viability, determined through the Tetrazolium (TZ) test, showed significant variation depending on the TZ concentration and staining duration. The highest viability (100%) was observed using 0.5% TZ solution after 4 hours of staining, establishing this combination as optimal for viability assessment. Imbibition studies revealed a progressive increase in seed fresh weight, following a characteristic triphasic pattern indicative of physiological readiness for germination. Germination experiments confirmed the absence of dormancy in A. marmelos seeds, indicating that no pre-treatment is necessary for successful germination. Storage behavior studies demonstrated that seeds dried to a moisture content of 4.58% and stored at –20°C retained viability above 86% after three months, confirming orthodox storage behavior. This finding contrasts with earlier reports suggesting intermediate seed storage characteristics. Overall, Aegle marmelos seeds exhibit high viability, favorable imbibition dynamics, and excellent storability, supporting their effective utilization in propagation and long-term conservation efforts.